Tanzania : Women in the Mining Sector - World Bank (Washington, DC, 2012)
The Government of Tanzania has, in recent years, focused on revitalizing its mining sector in order to attract foreign investment, with the goal of raising its contribution to Tanzania's Gross Domestic Product. With the support from the World Bank through the Mineral Sector Development Project (MSDP), the legal and fiscal regimes were revised and an environmental framework was put in place. As the growth of the small scale mining sub-sector continues, so do the challenges. This Notes discusses the obstacles faced by Tanzanian women and introduces the work of a women's nongovernmental organization -- Tanzania Women Miners Association (TAWOMA).